2017
DOI: 10.3174/ajnr.a5350
|View full text |Cite
|
Sign up to set email alerts
|

Brain Temperature Is Increased During the First Days of Life in Asphyxiated Newborns: Developing Brain Injury Despite Hypothermia Treatment

Abstract: BACKGROUND AND PURPOSE:Therapeutic hypothermia is the current treatment for neonates with hypoxic-ischemic encephalopathy. It is believed to work by decreasing the brain temperature and reducing the baseline metabolism and energy demand of the brain. This study aimed to noninvasively assess brain temperature during the first month of life in neonates with hypoxic-ischemic encephalopathy treated with hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
3
3
0
Order By: Relevance
“…Findings also suggest that infants with MRI evidence of injury had overall higher and more homogenous brain temperature than those without injury ( 97 ). Non-homogenous patterns of brain temperature were also shown in other studies ( 50 66 ). In infants developing brain injury after NE, hypothermia decreased brain temperature during the first days of life but did not prevent an early increase of brain temperature ( 66 ).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Findings also suggest that infants with MRI evidence of injury had overall higher and more homogenous brain temperature than those without injury ( 97 ). Non-homogenous patterns of brain temperature were also shown in other studies ( 50 66 ). In infants developing brain injury after NE, hypothermia decreased brain temperature during the first days of life but did not prevent an early increase of brain temperature ( 66 ).…”
Section: Discussionsupporting
confidence: 79%
“…Non-homogenous patterns of brain temperature were also shown in other studies ( 50 66 ). In infants developing brain injury after NE, hypothermia decreased brain temperature during the first days of life but did not prevent an early increase of brain temperature ( 66 ). Wu et al found significantly higher temperatures and brain-rectal temperature gradients in neonates with NE during TH ( 49 ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In the NICHD NRN childhood follow up data, the association with elevated temperature and death or IQ <70 was still present 30 . Brain temperature measured with magnetic resonance spectroscopy reveals a higher temperature among cooled infants with brain injury on magnetic resonance imaging (MRI) compared to cooled infants without brain injury on MRI 31 . Therefore it is important to avoid and treat elevations of temperature prior to and after TH.…”
Section: Management Of Elevated Temperaturementioning
confidence: 99%